A proposed single-stage single-phase full bridge boost inverter. Issue 1 (2nd January 2020) - Salem, Osama M.; Azazi, Haitham Z.; Osheba, Dina S. M.; Lashine, Azza E.
ABSTRACT: A proposed topology for a high-efficiency single-stage single-Phase boost inverter with a simple circuit configuration and a low component count is proposed in this paper. The proposed inverter produces instantaneous output voltages higher than the input dc voltage without an intermediate power conversion stage. A new control scheme is designed that enables the proposed inverter topology to produce a low distortion sinusoidal output waveforms and provide good load voltage regulation. The inverter circuit topology and modes of operations are fully described and simulated using Matlab/Simulink. The simulation results are presented illustrating the claimed boosting characteristics, sinusoidal output wave forms and good load regulation capability of the proposed inverter. The validity and effectiveness of the proposed inverter are verified experimentally by building a laboratory model using the digital signal processor (Model DS1104). The experimental results are presented confirming the claimed features of the inverter.